2021
DOI: 10.48550/arxiv.2110.01249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A physical model for the broadband energy spectrum of X-ray illuminated accretion discs: fitting the spectral energy distribution of NGC 5548

M. Dovciak,
I. E. Papadakis,
E. S. Kammoun
et al.

Abstract: Aims. We develop a new physical model for the broadband spectral energy distribution (SED) of X-ray illuminated accretion discs, that takes into account the mutual interaction of the accretion disc and the X-ray corona, including all the relativistic effects induced by the strong gravity of the central black hole on light propagation and on the transformation of the photon's energy, from the disc to/from the corona rest-frames, and to the observer. Methods. We assume a Keplerian, optically thick and geometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Finally, we let the inclination angle free to be determined during the fit, while its value was linked between the two periods. Although the improvement of the fit was not statistically significant, it is worth noting that the new fit resulted in a best-fit value of θ = 53.1 +7.7 −8.3 degrees, which is fully consistent with the value of θ = 55.9 +12.1 −6.9 degrees found by Dovciak et al (2021), who studied the average spectral energy distribution of NGC 5548.…”
Section: A Multi-epoch Analysissupporting
confidence: 84%
See 3 more Smart Citations
“…Finally, we let the inclination angle free to be determined during the fit, while its value was linked between the two periods. Although the improvement of the fit was not statistically significant, it is worth noting that the new fit resulted in a best-fit value of θ = 53.1 +7.7 −8.3 degrees, which is fully consistent with the value of θ = 55.9 +12.1 −6.9 degrees found by Dovciak et al (2021), who studied the average spectral energy distribution of NGC 5548.…”
Section: A Multi-epoch Analysissupporting
confidence: 84%
“…Furthermore, Dovciak et al (2021) found that the broadband spectral energy distribution of this source can also be well reproduced assuming an X-ray illuminated accretion disk. We may, therefore, conclude that the thermal reprocessing of X-rays by the disk is the most favorable physical scenario for driving the UV/optical variability at the considered time scales, at least in the case of NGC 5548.…”
Section: Psd Modelling Of Ngc 5548mentioning
confidence: 82%
See 2 more Smart Citations
“…for thermal reverberation in the accretion disc, where it is assumed that a fraction of the illuminating coronal X-rays are absorbed and thus the disc is heated (see, e.g. Kammoun et al 2019;Dovčiak et al 2021).…”
Section: Spectral Propertiesmentioning
confidence: 99%